ASSOCIATION BETWEEN SOCIAL MEDIA USE AND DEPRESSION AMONG U.S. YOUNG ADULTS. Issue 4 (19th January 2016) - Lin, Liu yi; Sidani, Jaime E.; Shensa, Ariel; Radovic, Ana; Miller, Elizabeth; Colditz, Jason B.; Hoffman, Beth L.; Giles, Leila M.; Primack, Brian A.
Abstract : Background: Social media (SM) use is increasing among U.S. young adults, and its association with mental well‐being remains unclear. This study assessed the association between SM use and depression in a nationally representative sample of young adults. Methods: We surveyed 1, 787 adults ages 19 to 32 about SM use and depression. Participants were recruited via random digit dialing and address‐based sampling. SM use was assessed by self‐reported total time per day spent on SM, visits per week, and a global frequency score based on the Pew Internet Research Questionnaire. Depression was assessed using the Patient‐Reported Outcomes Measurement Information System (PROMIS) Depression Scale Short Form. Chi‐squared tests and ordered logistic regressions were performed with sample weights. Results: The weighted sample was 50.3% female and 57.5% White. Compared to those in the lowest quartile of total time per day spent on SM, participants in the highest quartile had significantly increased odds of depression (AOR = 1.66, 95% CI = 1.14–2.42) after controlling for all covariates. Compared with those in the lowest quartile, individuals in the highest quartile of SM site visits per week and those with a higher global frequency score had significantly increased odds of depression (AOR = 2.74, 95% CI = 1.86–4.04; AOR = 3.05, 95% CI = 2.03–4.59, respectively). All associations between independent variables and depression had strong, linear, dose–response trends. Results were robust to all sensitivity analyses. Conclusions: SM use was significantly associated with increased depression. Given the proliferation of SM, identifying the mechanisms and direction of this association is critical for informing interventions that address SM use and depression.